2011
DOI: 10.1371/journal.pone.0020220
|View full text |Cite
|
Sign up to set email alerts
|

Pre-microRNA and Mature microRNA in Human Mitochondria

Abstract: BackgroundBecause of the central functions of the mitochondria in providing metabolic energy and initiating apoptosis on one hand and the role that microRNA (miRNA) play in gene expression, we hypothesized that some miRNA could be present in the mitochondria for post-transcriptomic regulation by RNA interference. We intend to identify miRNA localized in the mitochondria isolated from human skeletal primary muscular cells.Methodology/Principal FindingsTo investigate the potential origin of mitochondrial miRNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
263
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(268 citation statements)
references
References 51 publications
(64 reference statements)
4
263
0
1
Order By: Relevance
“…Indeed, theycan regulate pre-mRNA processing in the nucleus, act as chaperones to modify structure, or modulate mRNA-protein interactions [13]. while miRNAs generally function in the cytoplasm, they can be imported in the nucleus [14], in the mitochondrium [15], and even be secreted from the cell [16] or transferred from one cell to another [17,18]. Nevertheless, the relevance of subcellular localization for miRNA regulation is still a matter of study [19].…”
Section: The Complexity Of Micrornas (Mirnas) Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, theycan regulate pre-mRNA processing in the nucleus, act as chaperones to modify structure, or modulate mRNA-protein interactions [13]. while miRNAs generally function in the cytoplasm, they can be imported in the nucleus [14], in the mitochondrium [15], and even be secreted from the cell [16] or transferred from one cell to another [17,18]. Nevertheless, the relevance of subcellular localization for miRNA regulation is still a matter of study [19].…”
Section: The Complexity Of Micrornas (Mirnas) Biologymentioning
confidence: 99%
“…Mef2 promotes the expression of mitochondrial proteins that, in turn, induce mtTfa [40]. Intriguingly, the presence of several myomiRs translocated from the cytosol to mitochondria has been demonstrated in human skeletal muscle cells [15]. Among these, miR-133 was predicted to target the mitochondrial NADH dehydrogenase subunit 1 and was implicated in mitochondrial mRNA silencing [15] The comprehension of the role and regulation of miRNAs during cardiac development, as well as in pathological conditions in the adult, constitutes the basis for new targeted therapies for cardiac disease.…”
Section: Feedback Loops In the Regulation Of Myomirsmentioning
confidence: 99%
“…The human genome may encode over 1000 miRNAs [7]. In humans the miRNAs have been reported in mitochondria as well [8]. …”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…In addition, it is important to note that the expression pattern of mitomiRs may be tissue specific. In their study, Barrey et al 56 identified mitomiRs that are enriched in myoblasts, while another study reported cardiac-specific mitomiRs. 57 Therefore, it is possible that some mitomiRs may be expressed specifically in the breast.…”
mentioning
confidence: 97%
“…Barrey et al 56 have identified 243 miRNA in the mitochondrial RNA fraction. Intriguingly, three miRNAs, miR-146a, miR-103, and miR-16, were found in the IMS.…”
mentioning
confidence: 99%